The player - Tolkin, Michael 1950-; Newman, Thomas 1955- (The Criterion collection, 2016)
A Hollywood studio executive with a shaky moral compass (Tim Robbins) finds himself caught up in a criminal situation that would be right at home in one of his movie projects, in this biting industry satire from Robert Altman. Mixing elements of film noir with sly insider comedy, "The Player", based on a novel by Michael Tolkin, functions as both a nifty stylish murder story and a commentary on its own making, and it is stocked with a heroic supporting cast (Peter Gallagher, Whoopi Goldberg, Greta Scacchi, Dean Stockwell, Fred Ward) and a lineup of star cameos that make for an astonishing Hollywood who’s who. This complexly woven grand entertainment (which kicks off with one of American cinema’s most audacious and acclaimed opening shots) was the film that marked Altman’s triumphant commercial comeback in the early 1990s.
Original: USA 1992
Bildformat 1.85:1
Two-DVD special edition features: new 4K digital restoration ; audio commentary from 1992 featuring director Robert Altman, writer Michael Tolkin, and cinematographer Jean Lépine ; interview with Altman from 1992 ; new interviews with Tolkin, actor Tim Robbins, associate producer David Levy, and production designer Stephen Altman ; Cannes film festival press conference from 1992 with cast and crew ; Robert Altman's Players, a short documentary about the shooting of the film's fund-raiser scene ; map to the stars, a gallery dedicated to the cameo appearences in the film ; deleted scenes and outtakes ; the film's opening shot, with alternate commentaries by Altman, Lépine, and Tolkin ; Trailers and TV spots ; Plus: an essay by author Sam Wasson
Keywords: Film; DVD-Video